2008
DOI: 10.1111/j.1530-0277.2008.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Recent Alcohol Use and Sexual Behaviors: Gender Differences Among Sexually Transmitted Disease Clinic Patients

Abstract: Background Binge drinking is associated with risky sexual behaviors and STDs. Few studies have investigated this by gender or in an STD clinic. This cross-sectional study examined the association between binge drinking and risky sexual behaviors/STDs among patients attending an urban STD clinic. Method 671 STD clinic patients were tested for STDs, and queried about recent alcohol/drug use and risky sexual behaviors using audio computer-assisted-self-interview. The association between binge drinking and sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
97
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 33 publications
8
97
1
Order By: Relevance
“…11,27 The frequency of heavy drinking episodes at high school predicted drinking levels at university, as previously reported. 3 However, high school binge drinking was also significantly associated with unsafe sex due to drinking at university, independently of current level of drinking.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…11,27 The frequency of heavy drinking episodes at high school predicted drinking levels at university, as previously reported. 3 However, high school binge drinking was also significantly associated with unsafe sex due to drinking at university, independently of current level of drinking.…”
Section: Discussionmentioning
confidence: 74%
“…For many it is a period of their lives where they are sexually active but not in long-term stable partnerships. 7 A number of cross-sectional and longitudinal studies of students have shown associations between heavy alcohol use and risky sexual behaviour [8][9][10][11] or experiencing sexual assault. 8,12 A review of college studies in 2002 9 concluded that drinking was strongly related to the decision to have sex and to have multiple or casual partners, but did not have a consistent relationship with condom use.…”
mentioning
confidence: 99%
“…The role of gender in the associations between alcohol and sexual behavior is inconsistent in the literature, [23][24][25][26] perhaps owing to the myriad gender-related factors involved in drinking, sexual behavior, and their association, such as social norms favoring heavier drinking and casual sexual activity for men. 27,28 Because condom use and contraception may each be differentially controlled by male and female partners, 29 understanding gender differences in the associations between drinking and sexual risk behavior is critical.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Present Study Although studies have examined drinking and sexual behavior, many have three methodological shortcomings: (1) focus solely on college students, (2) measurement of aggregate rather than event-level associations, and (3) failure to account for influences on both sexual activity and sexual risk. We sought to simultaneously examine several demographic predictors in both day-and event-level associations between the number of drinks (alcohol dose influences the association between alcohol consumption and sexual behavior 3,24,[58][59][60][61] ) and sexual behavior, including vaginal and/or anal sex without a condom. All analyses adjust for problem drinking, as some research indicates an effect of alcohol abuse on sexual risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Alarmingly, illicit drug use among adult African American men was higher than rates for African American men and women combined (13.7 % vs. 9.5 %) as well as the national average (13.7 % vs. 10.2 %). 4 Alcohol and drug use/abuse have been associated with multiple negative consequences, including high-risk sexual behaviors, [5][6][7][8][9] violence, [10][11][12] unintentional injury, 13,14 and premature death 15,16 among diverse populations. Therefore, it is important to examine factors that may contribute to increased substance use/abuse among African American men, especially due to the higher rates of illicit drug use in this population.…”
Section: Introductionmentioning
confidence: 99%